Ethical Design of a Robot Platform for Disabled Employees: Some Practical Methodological Considerations - Colombino, Tommaso; Gallo, Danilo; Shreepriya, Shreepriya; Im, Yesook; Cha, Seijin (Frontiers in Robotics and AI, 2021)
This paper provides an account of the process of developing a scenario involving the use of a robotic platform to enhance the work-experience of disabled employees. We outline the challenges involved in uncovering the potential unintended consequences of introducing elements of Artificial Intelligence, automation and robotics into a socially and ethically complex and potentially fragile scenario, and the practical challenges involved in giving a voice to vulnerable users throughout the design process. While an ideal case scenario would involve the disabled employees as much as possible directly in the design process, this can, realistically, be a challenge. In this paper we detail a particular methodological and analytic approach centered around ethnography and design fictions, designed to provide a deeper understanding of all the stakeholders involved in the scenario and encourage ethical reflection. Based on our findings, we argue that while it is relatively easy to adopt an a priori ethical stance through notions like inclusivity and accessibility, there are risks involved in making such a priori prescriptive with respect to the perspectives of different stakeholders in an applied research project. More specifically, we highlight the importance of understanding the broad organizational and bureaucratic properties of a business or workplace when devising HRI scenarios and tasks, and of bringing consideration of elements like business models, operating philosophy and organizational hierarchies directly into the design process.